Investigation of material removal rate and surface roughness in finishing of internal surfaces of AISI 304 L austenitic stainless steel pipes by magnetic abrasives - Caydas, Ulas; Celik, Mahmut; Koklu, Ugur (Gazi Univ, Fac Engineering Architecture, 2019)
With the developing technology, high precision parts are needed especially in industries such as medical, food, aerospace and automotive. An extra surface finishing process is required for the manufactured parts to have the desired high sensitivity. It is not possible to finish especially complex shaped, variable sections, long and small parts by conventional methods. Surface finishing of such parts is only possible with non-traditional finishing methods. Magnetic Abrasive Finishing (MAF) is one of the non-traditional finishing methods in which remove materials from surface via magnetic field and abrasive particles. This experimental study investigates the feasibility of finishing of interior surfaces of austenitic stainless steel, which is widely used in medical, food and automotive industries, by MAF. Experiments have been conducted on AISI 304L stainless steel tubes and the effects of process parameters such as ferrous particle size, abrasive particle size, finishing time, rotational speed and percentage of abrasives on process responses namely improvement ratio in surface roughness (IRSR) and material removal rate (MRR) was recorded. As a result, it is observed from the experiments that MRR values were increased with increasing of ferrous particle size, abrasive size, rotational speed and percentage of abrasive grids; whereas MRR was reduced in enhanced machining time. Furthermore, the surface roughness was improved 75% with selecting suitable machining conditions.
Manyetik aşindiricilarla AISI 304L östenitik paslanmaz çelik borularin iç yüzeylerinin bitirme işleminde talaş kaldirma orani ve yüzey pürüzlülü?ünün araştirilmasi
Keywords: Magnetic abrasive finishing; surface finishing; abrasive finishing; surface roughness; AISI 304L